KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI ANTARA PEMBELAJARAN ORGANISASI DAN KINERJA ORGANISASI - Amin, Muh. Sirojuddin; Athia , Ita; Hermawan, Agus; Handayati, Puji (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2023)
The snack food industry, which is included in the SMEs category, is currently a commodity that is in great demand by the market. UD Sumber Dwi Jaya is one of the SMEs operating in the snack food industry. With various efforts, we are starting to show good organizational performance after being impacted by Covid-19. This research aims to analyze the influence of organizational learning towards organizational performance which is mediated by job satisfaction. The number of respondents used was 38, which is a census method. The method used is SEM-PLS analysis. The role of job satisfaction is able to encourage the relationship between organizational learning and organizational performance. Although partial organizational learning is not able to improve organizational performance directly. The organization does not facilitate employees in learning, this is natural because UD Sumber Dwi Jaya is included in the MSME category. The results show that high job satisfaction can increase organizational performance.